Mycobacterial infections in solid organ transplant recipients. (September 2014) - Meije, Y.; Piersimoni, C.; Torre‐Cisneros, J.; Dilektasli, A. G.; Aguado, J. M.; ,
Abstract: Mycobacterial infections represent a growing challenge for solid organ transplant recipients (SOT). The adverse effects of tuberculosis (TB) therapy present a major difficulty, due to the interactions with immunosuppressive drugs and direct drug toxicity. While TB may be donor‐transmitted or community‐acquired, it usually develops at a latent infection site in the recipient. Pre‐transplant prevention efforts will improve transplant outcomes and avoid the complications associated with post‐transplant diagnosis and treatment. The present review and consensus manuscript is based on the updated published information and expert recommendations. The current data about epidemiology, diagnosis, new regimens for the treatment of latent TB infection (LTBI), the experience with rifamycins for the treatment of active TB in the post‐transplant period and the experience with isoniazid for LTBI in the liver transplant population, are also reviewed. We attempt to provide useful recommendations for each transplant period and problem concerning mycobacterial infections in SOT recipients.